Oral Healthcare Implications of Dedicated Online Communities: A Computational Content Analysis of the r/Dentistry Subreddit. Issue 5 (16th April 2021) - Britt, Brian C.; Britt, Rebecca K.; Hayes, Jameson L.; Panek, Elliot T.; Maddox, Jessica; Musaev, Aibek
ABSTRACT: The current study explores communication expressed by participants in a subreddit surrounding oral health care, moderated by dentists and dental hygienists. The corpus was analyzed through Leximancer, a computer-assisted program used for computational content analyses of large data sets. Users' personal disclosures about ongoing dental concerns, advice about others' self-care, and the role of interpersonal communication with and among health care providers emerged as dominant themes. The findings suggest that online communities may serve an important role that dentists are unable to fill in their limited interactions with individual patients. Such interaction spaces may therefore offer a fertile environment for future interventions to promote beneficial practices and achieve positive health-related outcomes.